2020
DOI: 10.1038/s41598-019-56936-4
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality to define the mechanisms linking symptoms with cognitive deficits in attention deficit hyperactivity disorder

Abstract: The mechanisms underpinning attentional deficits are only partially understood. Here we ask if shifts in a child's field of view (FOV) act as a mediator between symptoms of attention deficit hyperactivity disorder (ADHD) and associated cognitive anomalies, particularly in attentional processes. Real time measurement of shifts in FOV were obtained on 85 children (mean age 9.4 (SD 1.9) years; 45 with DSM 5-defined ADHD) as they completed the continuous performance task in a "virtual classroom". We extracted meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…Similar to Mangalmurti et al (2020) and Lev et al (2020) we found that eye-tracking during attention-demanding tasks, whether in a VR environment or traditional CPT demonstrate that ADHD is associated with slow disengagement from confidence intervals after removal of between-subject variability. Statistical significance denoted by "*" for p ≀ 0.05 and "**" for p < 0.001.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar to Mangalmurti et al (2020) and Lev et al (2020) we found that eye-tracking during attention-demanding tasks, whether in a VR environment or traditional CPT demonstrate that ADHD is associated with slow disengagement from confidence intervals after removal of between-subject variability. Statistical significance denoted by "*" for p ≀ 0.05 and "**" for p < 0.001.…”
Section: Discussionsupporting
confidence: 80%
“…This proof of principle project also did not contrast ADHD performance to a healthy comparison group, without ADHD. The VR classroom has repeatedly shown significantly worse performance in behavior our previous studies (e.g., Parsons et al, 2007;Adams et al, 2009) and others (e.g., Mangalmurti et al, 2020), suggesting that that these effects would likely discriminate between groups. We consider this project to be the first in the series of projects and recommend future studies conduct testing between ADHD and typically developing children to assess differences in eye-tracking performance within the VR classroom.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…While this may well be the case, we provide new evidence that hyperactivity in ADHD participants can also be objectively measured in lifelike situations where the participants are moving freely. Thus far, the focus has mostly been on head movements (see, e.g., Parsons et al, 2019;Mangalmurti et al, 2020). We selected controller motion as the hyperactivity measure, since it is more closely related to performing actions in the game, whereas head movements can also reflect visual search.…”
Section: Epeli Measures Reflecting the Adhd Core Symptomatologymentioning
confidence: 99%
“…As also reported by [55], eye movements should be examined along with head movements to understand attention and interaction more in-depth, since eyes can move differently. In addition, [44] studied the relationship between performance, sense of presence, and cybersickness, whereas [38] examined attention, more particularly ADHD with continuous performance task in a virtual classroom. However, both works are more in the clinical domain, which are relatively different from an everyday classroom setup.…”
Section: Related Workmentioning
confidence: 99%